Effectiveness of VHS Lernportal Platform as Self-Directed Media for German Reading Comprehension of Eleventh-Grade Students at SMA Negeri 7 Malang - Jihaan Aprilianah; Herri Akhmad Bukhori (Universitas Negeri Malang, 2026)
Digital learning platforms offer alternatives to support self-directed learning and enhance language skills. This study analyzes the effectiveness of VHS Lernportal as a self-directed learning medium for German Lesen (reading) skills among eleventh-grade students at SMA Negeri 7 Malang. Utilizing a quantitative approach with a quasi-experimental design, the study sampled 24 experimental and 32 control group students via purposive sampling. Data from pretests and posttests were analyzed using the Mann-Whitney U test and N-Gain score analysis. Results indicated a significant difference between groups based on N-Gain scores (p < 0.001), with the experimental group outperforming the control group. In conclusion, VHS Lernportal effectively serves as a self-directed learning medium to improve students' German reading proficiency.